Nurturing Healthy Media Consumption Habits in Early Childhood: A Social Campaign Approach - Lukitowati, Suci; Hanum, Aliyah Nur’aini; Yuliono, Agus (CHANNEL: Jurnal Komunikasi, 2023)
In contemporary society, the pervasive presence of digital devices has profoundly influenced the media consumption patterns of young children, presenting challenges and opportunities for their development. This study explores the impact of media content on early childhood and the urgent need for informed parental supervision. Utilizing a Research and Development (R&D) methodology, a comprehensive social campaign titled "Healthy Watching" was developed and implemented in Pontianak, Indonesia. The campaign aimed to empower parents, particularly mothers, with the knowledge and skills necessary to guide their children's media interactions effectively. Through educational seminars, videos, stickers, and social media platforms, the campaign fostered awareness about age-appropriate content, screen time limits, and the importance of active parental engagement. The campaign's efficacy was evaluated through stakeholder engagement and behavioral assessments of eight target mothers. The results indicate significant improvements in knowledge, attitudes, and behaviors, emphasizing the campaign's success in promoting healthy media consumption habits. This study provides valuable insights into the design and implementation of social campaigns to address the challenges of digital media in early childhood.